공기식 태양광/열 집열기 내 저항체 형상조건과 유동 조건에 따른 열전달 성능 및 압력강하 분석 - 김성빈(Kim Seongbhin); 김준엽(Kim Junyeop); 안병화(An Byunghwa); 김영복(Kim Youngbok); 손창효(Son Changhyo); 윤정인(Yoon Jungin); 최광환(Choi Kwanghwan) (한국태양에너지학회 논문집, 2022)
Air-type photovoltaic and thermal (PV/T) has a lower thermal capacity than liquid-type one; therefore, studies are being conducted turbulence promoters to improve heat transfer in a duct. This study aims to evaluate heat transfer performance and pressure drop while changing the increasing and decreasing ratio of turbulence promoters by using computational fluid dynamics (CFD). The increasing and decreasing ratio is a concept focused on increasing the height of turbulence promoters n times from the first row to the last row to generate high air temperatures at the outlet side. As a result, the difference in heat transfer performance according to the increasing and decreasing ratio was minimal; however, it was confirmed that the pressure drop increased in the order of 1.3, 1.2, and 1.1, because the increased resistance to air flow due to increased installation height of the turbulent promoters. Accordingly, it was found that the thermohydraulic performance parameter (THPP) increased in the order of 1.1, 1.2, and 1.3. Because of the changes for various shape conditions were not taken into account, additional consideration is required to select suitable conditions. KCI Citation Count: 1